Compound odontoma associated to permanent teeth impaction in jaw: Case report - Meneses-Santos, Daniela; Góis, Andre Silva; Amorim, Klinger de Souza; Albuquerque Junior, Ricardo Luiz Cavalcanti; Souza, Liane Maciel de Almeida (Journal of Oral Diagnosis, 2018)
The odontoma is a benign tumor of odontogenic origin, is considered a developmental malformation (hamartoma). The compound odontoma is formed by all tissues of a normal tooth arranged in an organized manner. Odontomas have slow growth and are not aggres- sive; most are asymptomatic, being diagnosed in routine radiographs. This study aims to present a case report of compound odontoma associated with impaction of permanent teeth in the jaw. Treatment opted for the surgical removal of the compound odontoma and permanent impacted teeth.